INNOVATION OF OIL PALM PLANT WASTE IN THE VILLAGE OF PLANTATION FOR LOSS OF DISTRICT SIRAPIT STEP DISTRICT - Siregar, Rosnah; Hodriani, Hodriani (Universitas Negeri Medan, 2018)
AbstractThe partner in the PKM program is the group of working housewives at Amal Tani Plantation village, Sirapit District, Langkat Regency. Based on the observation in the village, there are a lot of palm sticks wastes from the palm plantation. The interview carried out to the creative housewives resulted in some problems that they face, namely: (1) their husbands work only as the labor in the palm plantation, so the income is not sufficient for the family, (2) the knowledge of the women about the palm sticks waste from the palm plantation is still low, (3) the knowledge in business management is still low as well, (4) there are no special production tools in making tissue boxes, bags, and purses. The solutions proposed to solve the problem of the partner are: (1) empowering the group of creative housewives by using the resources in the village such as the sicks waste from the palm plantation for gardening rib-broom, bedroom rib- broom, plates, fruit basket, mineral water container, bag, and purse. (2) training about the rib waste from the palm plantation and the accompaniment followed-up by the practice to process the sticks waste from the palm plantation by presenting a competent source, (3) training and the accompaniment of business management in marketing and accounting, (4) providing the production tools and design making and the other kinds of handicraft made of rib waste from the palm plantation. The success of the service program will be measured from the output, such as: (1) the guidance of using the sticks waste from the palm plantation to become the gardening rib broom, bedroom rib broom, plate, fruit basket, tissue box, purse and bag, (2) product innovation from the sticks waste of the palm plantation, such as the yard broom, bedroom broom, plate, fruit basket, tissue box, purse and bag, (3) the report of the financial transaction in the cash book, (4) production tools to make the tissue box, purse, and bag by using ATBM.Keywords: Empowerment, Accompaniment, Palm Stick Waste, Product Innovation.